2018
DOI: 10.1038/s41437-018-0073-2
|View full text |Cite
|
Sign up to set email alerts
|

Speciation in the presence of gene flow: population genomics of closely related and diverging Eucalyptus species

Abstract: Speciation is a complex process that is fundamental to the origins of biological diversity. While there has been considerable progress in our understanding of speciation, there are still many unanswered questions, especially regarding barriers to gene flow in diverging populations. Eucalyptus is an appropriate system for investigating speciation mechanisms since it comprises species that are rapidly evolving across heterogeneous environments. We examined patterns of genetic variation within and among six close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 87 publications
5
53
2
Order By: Relevance
“…About half of all common variants discovered in this study are common in both species, and we observed low genome‐wide divergence between E. albens and E. sideroxylon ( F ST = 0.15). Recent evidence suggests the genetic divergence is not strong at most genomic loci in many species, both in eucalypts (Rutherford et al, ) and more broadly (Andrew & Rieseberg, ; Wu, ). Additionally, low interspecific differentiation is expected theoretically given extremely large effective population sizes, long generation times and relatively recent radiation (González‐Orozco et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…About half of all common variants discovered in this study are common in both species, and we observed low genome‐wide divergence between E. albens and E. sideroxylon ( F ST = 0.15). Recent evidence suggests the genetic divergence is not strong at most genomic loci in many species, both in eucalypts (Rutherford et al, ) and more broadly (Andrew & Rieseberg, ; Wu, ). Additionally, low interspecific differentiation is expected theoretically given extremely large effective population sizes, long generation times and relatively recent radiation (González‐Orozco et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced representation sequencing approaches, such as DArTseq, enable the cost‐effective investigation of evolutionary processes at a genomic scale and the fine‐scale examination of genetic variation across landscapes (Bragg et al ). Recent studies using DArTseq have found that they are informative for understanding relationships among populations and species, particularly in closely related lineages (Yang et al ; Melville et al ; Rutherford et al ).…”
Section: Methodsmentioning
confidence: 99%
“…About half of all common variants discovered in this study are common in both species, and we observed low genome-wide divergence between E. albens and E. sideroxylon (F ST = 0.15). Recent evidence suggests the genetic divergence is not strong at most genomic loci in many species, both in eucalypts (Rutherford et al, 2018) and more broadly (Andrew and Rieseberg, 2013;Wu, 2001). Additionally, low interspecific differentiation is expected theoretically given extremely large effective population sizes, long generation times, and relatively recent radiation (González-Orozco et al, 2016).…”
Section: Interspecific Divergence and Gene Flowmentioning
confidence: 99%
“…The prevalence of discrete population structure, IBD and/or IBE has been studied in several eucalypt species (e.g. Andrew et al, 2005Andrew et al, , 2007Jones et al, 2007;Jordan et al, 2017;Rutherford et al, 2018;Steane et al, 2006Steane et al, , 2015Steane et al, , 2014Supple et al, 2018). Although eucalypts have very limited seed dispersal, they generally preferentially outcross and are pollinated by generalist bird and insect pollinators, both of which contribute to their spatial genetic structure (Booth, 2017;Potts and Gore, 1995;Williams and Woinarski, 1997).…”
Section: Introductionmentioning
confidence: 99%